Determinantes da propensão ao endividamento: um estudo nas mulheres da mesorregião centro ocidental rio grandense - Trindade, Larissa de Lima (2009)
Currently, the decisions taken by individuals as the act of buying, selling, consuming, saving and debt has been the focus of many scientific lines. From the viewpoint of Behavioral Finance, this study aims to analyze what are the determining factors in the propensity to indebtedness among women in the Mesorregião Centro Ocidental Rio-grandense. For this, a survey was conducted among 2,500 women distributed statistically in 31 municipalities of Mesorregião. Data were collected through questionnaire and analyzed via factor analysis, statistical tests (Anova, Correlation Test) and regression analysis. The results showed seven factors related to the values of money they are: Social Status, Concern, Stability, Pleasure, Power, Budget and Illusion is a factor for materialism and a factor for the debt. The women studied had higher average for the budget factor which indicates a certain empreendedor control of their spending, which agrees with this, it was also found low levels of debt and materialism in women from the middle region studied, however, higher for women living outside Santa Maria. It is emphasized that these low levels of materialism in the area surveyed is strongly linked to aspects of colonization, mainly coming from the Italian culture and the actual level of financial literacy shown by interviews. The ANOVA showed there are differences in the average propensity to factor Indebtedness, when analyzed under the aspects of religion, ancestry, race, debts and other variables. Regression, we obtained a percentage of explanation of the dependent variable (propensity to indebtedness) of 39.1% through the following independent variables: Material Factor, Concern Factor, Factor Budget, Dummy has Debts, Power Factor, Dummy has Liabilities in Delay and Dummy Hourglass. It is noteworthy that the budget factor in the propensity to interfere with Indebtedness negative sign, that is, as this increases the propensity decreases and all other variables have positive sign. Overall, this study showed that on average, women in Mesorregião observed, are little prone to debt and the factors that interfere with this tendency are not only financial and rational, but also psychological and cultural.